Managing university rank and tenure decisions using a multi-criteria decision-making approach. (20th March 2019) - Mu, Enrique; Nicola, Cynthia Busin
Faculty evaluation in academia is a serious concern for higher-education administrators. This study develops a model for rank and tenure (R&T) decisions using an analytic hierarchy process (AHP) multi-criteria decision-making (MCDM) approach. Literature review suggests most R&T evaluations are rather subjective in many institutions. A case method approach is used for the development of a model and demonstration of its use. The proposed evaluation model provides objectivity, transparency and customisation for R&T committee decisions in higher-education institutions.